Predictors of constrictive pericarditis after tuberculous pericarditis. - Suwan, P. K. (1995)
OBJECTIVE--To identify features which predict the subsequent development of constrictive pericarditis from acute or subacute tuberculous (TB) pericarditis. SETTING--Tertiary referral centre, chest hospital. PATIENTS--The records of 16 consecutive patients in whom acute or subacute TB pericarditis was diagnosed between 1988 and 1990 at a chest hospital were reviewed. These records included a follow up of at least 12 months. RESULTS--During a follow up of 14.2 (12-30) months, 8 patients had constrictive pericarditis diagnosed by cardiac catheterisation or by inspection at the time of operation (group A). There was no evidence of constriction in the other eight patients (group B). There was no significant difference between the two groups in the type or duration of symptoms of TB pericarditis before admission or the volume and characteristics of pericardial fluid obtained at hospital admission. Clinical features of cardiac tamponade on admission correlated closely with the subsequent development of constrictive pericarditis requiring pericardectomy (7/8 v 2/8; P = 0.01), despite the fact that the signs of tamponade resolved completely after pericardiocentesis. CONCLUSION--The findings suggest that cardiac tamponade in the early clinical stage of TB pericarditis is the most predictive factor of subsequent constrictive pericarditis. The degree of fibrosis of pericardium when treatment starts may be the most important determinant of whether or not constriction develops.